MENINGKATKAN PEMAHAMAN SISWA TENTANG WUJUD BENDA MELALUI PENGGUNAAN METODE DEMONSTRASI - Siti Sahronih; Desti Noor Apifah (PERISKOP : Jurnal Sains dan Ilmu Pendidikan, 2021)
In an effort to improve student learning outcomes about the shape of objects in this study, learning is presented through the use of demonstration methods that can help students to understand the shape of objects. This research is Classroom Action Research with the research subjects being students of SD Negeri Karanglayung. Each cycle consists of four activities, namely planning, implementation, observation, and reflection. The instruments used are test results of learning and observation. Learning outcomes test is used to measure the success of learning in an effort to improve student learning outcomes about the shape of objects through the use of demonstration methods in Natural Science subjects in elementary schools. The teacher uses a demonstration method that can help students in an effort to improve student learning outcomes, starting from conditioning students' readiness related to the material, explaining the subject matter in detail and carrying out evaluations and the results obtained from this study show a better improvement.